Comprehensive Determination of Pharmaceuticals, Personal Care Products, Benzotriazole UV Stabilizers and Organophosphorus Flame Retardants in Environmental Water Samples Using SPE Coupled with UHPLC-MS/MS - Kim, Joon-Woo; Isobe, Tomohiko; Tanoue, Rumi; Chang, Kwang-Hyeon; Tanabe, Shinsuke (Current Analytical Chemistry, 2015)
A high throughput and sensitive analytical method for the comprehensive determination of 31 environmental contaminants (10 pharmaceuticals and personal care products, PPCPs; 8 benzotriazole UV stabilizers, BUVSs; and 13 organophosphorus flame retardants and plasticizers, PFRs) in aqueous sample using solid phase extraction (SPE) followed by ultra-high-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UHPLC-ESI-MS/MS) was developed. The optimized method was applied to aqueous samples and the limits of quantification (LOQs) ranged from 1.9 to 16 ng L-1 and from 2.3 to 45 ng L-1 in river water and effluent of sewage treatment plant (STP), respectively. All the correlation coefficients of the calibration curves were equal or greater than 0.99 in the range of 0.01-10 μg L-1. Oasis HLB (60 mg) cartridge showed the highest recoveries for all the analytes in river water (71- 115%) as well as in wastewater (71-117%) except for dibenzyl phosphate (DBzP) (58%). The intra- and inter-day repeatabilities were less than 14% at the two spiked levels (100 and 500 ng L-1). The developed method was applied for the determination of these target compounds in river water and STP effluent collected from Kumamoto, Suya and Matsuyama, Japan. Of the thirty-one compounds monitored, seventeen were found in one or more samples, especially diclofenac (DF) and carbamazepine (CBZ) were detected in all the water samples.
Keywords: water